Establishment of Desmodium ovalifolium on an ultisol - Abd Halim, Mohd Ridzwan; Othman, Sariam (Universiti Pertanian Malaysia, 1982)
The effect of various scarification treatments on the germination of seeds of Desmodium ovalifolium (Prain) was studied. Following this a pot trial was conducted to evaluate the effects of lime, phosphorus and Rhizobium inaculation on the dry matter yield, nodulation and the nitrogen and phosphorus content in the plant. Mechanical scarification by abrasion with sandpaper improved germination by 30 percent. Liming up to the highest level of 1000 kg/ha significantly increased dry matter yield and nodulation. Phosphorus increased nodule number and phosphorus content in leaves and stems. Inoculation increased dry matter yield, nodulation and the levels of nitrogen and phosphorus in the leaves and stems.